Renormalization group meshes and the discretization of TCAD equations. - Schoenmaker, W. (IEEE Transactions on computer-aided design of integrated circuits and systems)
This paper presents a new method to discretize the equations for the physical modeling of semiconductor devices and back-end patterns. The method assembles planes in two dimensions and cubes in three dimensions and allows for adaptive meshing without the occurrence of spurious nodes due to mesh smoothing. Whereas the applications that are discussed focus on the design of microelectronic devices, the method is generally applicable to all fields of engineering where ab initio physical modeling is required.